Digitalisasi Lokasi SMK Di Kota Padang Menggunakan Web Gis - adha, Hasbi; Sularno, Sularno; Fardika, Faradika (Jurnal Sistem Informasi Dan Informatika, 2023)
The city of Padang is the capital of the province of West Sumatra and also the city of education in the province of West Sumatra. Karna is the capital of the province of West Sumatra, the city of Padang has a very good education. How many problems do people who continue their education in the city of Padang get? An educational website records that there are around 191,155 students scattered throughout the city of Padang. Why so many, because the city of Padang is the capital city of West Sumatra province, therefore, the city of Padang has become an educational destination for village children to study in the city. Digitizing the location of the high school in Padang city is expected to be a solution for students who are looking for or Hakan who doesn't know the location of the SMA in Padang city. In this system, users only need to open the digitalization of the location of the vocational school on their smartphone when they come to the city of Padang, then the existing system will direct the user to take the path that is closest to the vocational school that students are looking for from outside or from within the city of Padang. This will make it very easy for users to find the location of the school they want to go to.